2019
DOI: 10.1073/pnas.1821552116
|View full text |Cite
|
Sign up to set email alerts
|

Inositol polyphosphates promote T cell-independent humoral immunity via the regulation of Bruton’s tyrosine kinase

Abstract: T cell-independent (TI) B cell response is critical for the early protection against pathogen invasion. The regulation and activation of Bruton’s tyrosine kinase (Btk) is known as a pivotal step of B cell antigen receptor (BCR) signaling in TI humoral immunity, as observed in patients with X-linked agammaglobulinemia (XLA) experiencing a high incidence of encapsulated bacterial infections. However, key questions remain as to whether a well-established canonical BCR signaling pathway is sufficient to regulate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 53 publications
1
20
0
1
Order By: Relevance
“…DMR detection found 100 DMRs, which were associated with 70 unique genes and 6 enriched pathways (phosphatidylinositol signaling, axon guidance, inositol phosphate metabolism, calcium signaling and IL-17 signaling pathway, Figure 2 D). Similar genes are involved in phosphatidylinositol signaling, inositol phosphate metabolism and calcium signaling, which play many crucial roles in diverse cellular functions including immune responses [ 15 , 16 ]. IL-17 signaling is also a key pathway in regulating immunity [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…DMR detection found 100 DMRs, which were associated with 70 unique genes and 6 enriched pathways (phosphatidylinositol signaling, axon guidance, inositol phosphate metabolism, calcium signaling and IL-17 signaling pathway, Figure 2 D). Similar genes are involved in phosphatidylinositol signaling, inositol phosphate metabolism and calcium signaling, which play many crucial roles in diverse cellular functions including immune responses [ 15 , 16 ]. IL-17 signaling is also a key pathway in regulating immunity [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the direct products of IPMK, its downstream IP products, including IP6, have been suggested to mediate cellular signaling. For example, in IPMK knock-out (KO) murine B cells, reductions in the level of IP6, a cofactor required for Btk kinase activation, impaired Btk activation and B-cell receptor signaling (Kim et al, 2019). The lipid-kinase activity of IPMK (i.e., a PI3-kinase) expands the signaling role of IPMK in mammals (Table 1).…”
Section: Action Modes Of the Ipmk Signalingmentioning
confidence: 99%
“…IPMK is a key determinant in stabilizing TRAF6 by preventing the ubiquitination-dependent proteasomal degradation of this TLR signaling factor, thereby influencing the TLR-induced innate immunity. Bacterial polysaccharides and the repetitive epitopes of viral particles can activate B cells independently of T cells via cross-linking of the antigen receptors (Kim et al, 2019). This process triggers a rapid and robust antibody response to bacterial infection.…”
Section: Neural Controlmentioning
confidence: 99%
“…Moreover, an in vivo study demonstrated the immunomodulatory function of IP6 in B cells. Indeed, IP6 (80 μM) activated T cellindependent humoral immunity by improving B cell antigen receptor (BCR) signaling (W. Kim et al, 2019b).…”
Section: Phytic Acidmentioning
confidence: 99%